Failures in earthworks proceedings of the Symposium on Failures in Earthworks organized by the Institution of Civil Engineers and held in London, 6-7 March 1985. (Thomas Telford, 1985)
Aimed at civil engineers, these papers highlight failures and repairs in earthworks, look at formation failures, rock slopes and conclude with serviceability failures.